Policy entry points for healthy diets in India: Insights from three consultations - Kishore, Avinash; Swaminathan, Soumya; Scott, Samuel P.; Avula, Rasmi; Menon, Purnima (International Food Policy Research Institute, 2025)
Improving diet quality in India is both urgent and achievable, and the cost of inaction is high. The policy entry points identified through stakeholder consultations offer practical ways forward—from implementing front-of-package labeling and restricting ultra-processed food advertisements, to strengthening nutrition behavior change communication in existing safety net programs and making these programs more nutrition-sensitive. India's increasingly diverse food production is creating the supply-side foundation for healthier diets. Policy action should now focus on three key areas: making nutritious foods more accessible and affordable through agricultural policies and social protection programs that enable and incentivize crop and diet diversification; fostering healthier food environments by regulating ultra-processed foods with improved labeling, restrictions on advertising and promotion near schools, and limits on sugar, fat, and salt content; and building sustained demand for diverse, nutritious diets through targeted behavior change communication. Implementation should apply a consistent equity lens: prioritizing lagging geographies and marginalized groups, addressing gendered time constraints through childcare and other supports, and enabling women-led and small enterprises that produce nutritious, convenient foods. Success requires prioritizing cost-effective interventions with demonstrated impact, fostering collaboration across government departments and levels, and leveraging India's growing data infrastructure to ensure interventions reach the most vulnerable populations.